The Phenomenon of Guzel Yakhina: on the Reception of the Novel „Zuleikha Opens her Eyes” - Sitnikova, Vera (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article analyzes salient aspects of Guzel Yakhina’s novel Zuleikha (Zuleikha opens her eyes) and its critical reception. First of all, the author discusses the connections of the artistic world of the novel with the Russian literary tradition with respect to the image of “the natural man”. Particular attention is paid to the treatment of the “eternal themes” of love, motherhood, faith, the formation of personality as well as to the originality with which the author approaches the topic of the mass repression of the 1930s. The predominating opinions of critics and reviewers are interpreted, and an attempt is made to indicate the reasons for the novel’s popularity with the readers.